ASSESSMENT OF ORAL HYGIENE HABITS IN CHILDREN 6 TO 12 YEARS. - Liliya Doichinova; Nadezhda Mitova (Peytchinski Publishing, 2014)
INTRODUCTION: Oral hygiene is an essential element of health education programs for schoolchildren. AIM: The study aims to assess the skills when conducting oral hygiene of a group of schoolchildren and to conduct training in its rules. MATERIAL AND METHODS: The study covers 30 children aged 6-12 years. The training was conducted by the methods of the visual pedagogy and implementation of the technique "Say, show, do". The assessment of the oral-hygiene status was held by the simplified oral hygiene index-Greene & Vermillion. RESULTS AND CONCLUSION: The children do not have proper oral hygiene habits. The daily oral care is inadequate. The number of cleaned tooth surfaces during oral hygiene practice is small. Children have no developed proper oral hygiene skills, and brush only the vestibular surfaces of the teeth (80%), 13.3% the vestibular and the occlusal, and 6.7% only cover lingual surfaces too. The unsatisfactory oral hygiene status is also a result of using only one type of toothbrush movements. The improvement of children's health knowledge should play key role in correcting their oral hygiene technique.